Validation of physiological tests in relation to competitive performances in elite male distance cross-country skiing - Carlsson, M.; Carlsson, T.; Hammarström, D.; Tiivel, T.; Malm, C.; Tonkonogi, M. (The Journal of Strength and Conditioning Research, 2012)
The purpose of the present study was to establish which physiological test parameters reflects the distance performances in the Swedish National Championships in cross-country skiing (SNC) and the International Ski Federation's ranking points for distance performances (FISdist). The present study also aimed to create multiple regression models to describe skiing performance for the SNC distance races and International Ski Federation's (FIS) ranking. Twelve male, Swedish, national elite, cross-country skiers (maximal oxygen consumption [VO2max] = 5.34 ± 0.34 L/min) volunteered to participate in the study. Their results in the 2008 SNC (15 km race [SNC15] and 30 km race [SNC30]) and FISdist points were used as performance data. On the week preceding the Championship, subjects completed a test battery consisting of 7 physiological tests: isokinetic knee extension peak torque (PT), vertical jumps (VJ), lactate threshold (LT), VO2max, and 3 double poling tests of different durations (DP20, DP60, and DP360). Correlations were established using Pearson's correlation analysis, and models to describe skiing performance were created using standard multiple linear regression analysis. Significant correlations were found between the performance parameters and test parameters derived from LT, VO2max, and DP60 tests. No correlations with any performance parameter were found for PT, VJ, DP20, and DP360 tests. For FISdist and SNC15, the models explain 81% and 78% of the variance in performance, respectively. No statistically valid regression model was found for SNC30. The results of this study imply that the physiological demands in male elite distance cross-country skiing performances are different in different events. To adequately evaluate a skier's performance ability in distance cross-country skiing, it is necessary to use test parameters and regression models that reflect the specific performance.